The Excised Appendix Tip—To Send or not to Send, That is the Question - Tullie, Lucinda; Vadgama, Bhumita; Anbarasan, Ravindar; Stanton, Michael P.; Steinbrecher, Henrik (European Journal of Pediatric Surgery Reports, 2018)
A 9-year-old boy, with previous anorectal malformation and neuropathic bladder and bowel, underwent ileocystoplasty, Monti–Mitrofanoff and appendix antegrade colonic enema procedure. The tip of the macroscopically normal appendix was sent for routine histopathology. Microscopy demonstrated a 5-mm well-differentiated neuroendocrine tumor extending into muscularis propria. Ki-67 index was <2%. Due to margin involvement, the appendix conduit and surrounding skin were re-excised and a tube cecostomy was created through a separate incision. Microscopy revealed no residual neuroendocrine tumor, and no further treatment was required.
Keywords: appendix; carcinoid; pediatric; antegrade continence enema